Estimation of morphological characteristics of Rio pear orange acquired in the local trade of Alta Floresta - MT through image analysis - Farias, C. B. M.; Correa, A. S. A. S.; Silva, M. C. M.; Cruz, R. R.; Ramos, L. P. N.; Souza, S. A. M. (Scientific Electronic Archives, 2020)
Citrus fruits are among the most consumed fruits by Brazilians, being grown in practically all states. Phenotyping has been associated with non-destructive optical analysis of plant characteristics, due to the use of images. The present study had the objective of estimating the morphological characteristics of Pera Rio orange fruits (Citrus sinensis) acquired in the local trade of Alta Floresta through traditional methods and using the Tomato Analyzer softwer. Measurements were made regarding length and width with the aid of a digital caliper, fruit mass using a digital precision analytical balance, total soluble solids content (ÂºBrix), skin thickness and height of the endocarp. The volume was also measured using the water column displacement method (VDCA), estimated diameter values with the Tomato Analyzer program, the correlation between the volumes was performed, and regression model estimates were performed based on the SigPlot program. . It was found that there was a correlation between volume estimation by the water column displacement method (VDCA) and fruit volume using the diameter estimated by the digital image (IPV), revealing that the R2 correlation coefficient was 0.80. Through the obtained results it is possible to state that the Tomato Analyzer is efficient to evaluate the volume of orange Pera Rio fruits, being able to be indicated to characterize other citrus fruits.